2014
DOI: 10.1111/een.12175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental warming on survival, phenology, and morphology of an aquatic insect (Odonata)

Abstract: 1. Organisms can respond to changing climatic conditions in multiple ways including changes in phenology, body size or morphology, and range shifts. Understanding how developmental temperatures affect insect life-history timing and morphology is crucial because body size and morphology affect multiple aspects of life history, including dispersal ability, while phenology can shape population performance and community interactions. 2. We experimentally assessed how developmental temperatures experienced by aquat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 77 publications
9
64
1
Order By: Relevance
“…These studies have found that growth rates increase in warmer temperatures (except see Van Doorslaer and Stoks 2005a), an expected result because ectotherm growth rates are known to scale allometrically with temperature (Angilletta et al 2004). Faster growth rates are likely to underlie observed patterns of advancing phenology, such as earlier adult emergence in odonates (Hassall et al 2007;McCauley et al 2015). Whether accelerated growth rates in the context of a warming environment has net benefits or costs for populations will depend on the species and the ecological context in which these animals exist.…”
Section: The Effects Of Temperature On Inter-and Intra-specific Egg Dmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have found that growth rates increase in warmer temperatures (except see Van Doorslaer and Stoks 2005a), an expected result because ectotherm growth rates are known to scale allometrically with temperature (Angilletta et al 2004). Faster growth rates are likely to underlie observed patterns of advancing phenology, such as earlier adult emergence in odonates (Hassall et al 2007;McCauley et al 2015). Whether accelerated growth rates in the context of a warming environment has net benefits or costs for populations will depend on the species and the ecological context in which these animals exist.…”
Section: The Effects Of Temperature On Inter-and Intra-specific Egg Dmentioning
confidence: 99%
“…Increases in temperature as a result of climate change could potentially add additional sources of mortality to populations that already have low larval survival (Cornell and Hawkins 1995;Hirst and Kiørboe 2002;Forster and Hirst 2012). Temperature appears to increase odonate mortality when larvae develop and metamorphose in heated conditions (McCauley et al 2015). These types of studies, however, often do not track survival throughout development and therefore it remains unclear at what stage mortality is occurring.…”
Section: The Effects Of Temperature On Inter-and Intra-specific Egg Dmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of other odonate responses to climate change have also been documented, including body size reductions (Forster, Hirst, & Atkinson, 2012), northerly range shifts (Flenner&Sahlén, 2008; Grewe, Hof, Dehling, Brandl, & Braendle, 2013; Hickling, Roy, Hill, & Thomas, 2005), and advancing phenologies (Dingemanse & Kalkman, 2008; Hassall, Thompson, French, & Harvey, 2007). Larval dragonflies exposed to experimental warming show a range of responses including increased mortality and advancing phenologies (McCauley, Hammond, Frances, & Mabry, 2015; Richter, Suhling, Mueller, & Kern, 2008; Suhling, Suhling, & Richter, 2015). Further, there is evidence of variation between odonate species in response to warming (Suhling & Suhling, 2013).…”
Section: Introductionmentioning
confidence: 99%